Properties of Wheat Straw Fiber Board Made Using Pulverized And Alkali Treated Straw - MAMATHA, B.S.; SUJATHA, D.; UDAY, D.N.; KIRAN, M.C. (Indian Forester, 2023)
Need to source alternative raw materials for panel industry has led to the study of wheat straw for the manufacturing of Medium Density fiber board (MDF). Wheat straw with alkali treatment (0.1 and 0.3%) was studied for the manufacturing of Medium Density Fiber (MDF) board. Characterisation of fibers were carried out using fiber analyser. MDF panels were made using 10% and 12% Urea formaldehyde resin (UF) and 10% Meiamlne urea formaldehyde resin (MUF). Physical and mechanical properties were evaluated as per IS 12406-2003. Study infers that alliaii treated fibers has shown improved properties with 12% UF resin bonded MDF boards. The results showed that the physical & mechanical properties MUF resin bonded wheat straw fibre boards meet the requirements of MDF as per IS-12406-2003 standards.